Damage of Clove Trees Caused by Stem Borer Attack (Nothopeus hemipterus) in Central Peling Subdistrict, Banggai Kepulauan District - Kulendeng, Jeksen; Basir, Muhammad; Asrul, Asrul (Universitas Tadulako, 2021)
Clove (Syzigum aromaticum L.) is a native Indonesian plant originating from the Maluku Islands. Until now, cloves have become an essential commodity to support the industry and as sources of farmers' income. An increase followed the increasing area of clove cultivation in problems caused by stem borer attack (Nothopeus Hemipterus). This research aims to obtain information about the magnitude of damage intensity and the extent of stem borer attack. This research was conducted in two village areas: Alakasing village and Solongan village in Central Peling Subdistrict of Banggai Kepulauan District for three months on July 3 - 18, 2017. The observations were carried out on ten plantations owned by farmers: five farms in Alakasing village and five farms in Solongan village. Each sample plot was observed 20 sample plants so that obtained 200 sample plants, the strata of each tree is devided. The highest pest attack area (Nothopeus hemipterus) is in Alakasing Village, plot sample I of the sixth observation is 75%, and the lowest pest attack area (Nothopeus hemipterus) is plot sample V of the sixth observation. Whereas in the observation area of the Solongan Village, the highest percentage of attack area in sample V of the sixth observation is 30% and the lowest percentage of pest attack area (Nothopeus hemipterus) sample plots I and IV respectively 20%. The percentage of damage intensity caused by clove stem borer (Nothopeus hemipterus) in the Alakasing village area was 7.56%, while the percentage of damage intensity in the Solongan Village area is 3.26%.